1998
DOI: 10.1046/j.1365-2303.1998.00134.x
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for anal cytology—to make cytological diagnosis and follow up much more reliable

Abstract: Anal intraepithelial neoplasia is a difficult diagnostic and management problem, particularly when it occurs in women with synchronous or metachronous genital intraepithelial neoplasia. Diagnosis and follow up by colposcopy is too specialized for widespread use, and although anal cytology has been used before it has been thought of as too inconsistent for practical application. This study standardized collection of specimens and investigated interobserver variation. The aim of the study was to determine whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 10 publications
(11 reference statements)
0
15
0
2
Order By: Relevance
“…26,27 Few studies have evaluated the reliability of anal specimen reporting. [17][18][19] Scholefield et al 17 circulated 30 cytology slides with material obtained from the perianal skin to 6 pathologists and reported point estimates of pairwise agreement ranging from 0.65 (moderate) to 1.00 (perfect). Carter et al 18 circulated 100 paraffin and fresh frozen histology slides to 5 pathologists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 Few studies have evaluated the reliability of anal specimen reporting. [17][18][19] Scholefield et al 17 circulated 30 cytology slides with material obtained from the perianal skin to 6 pathologists and reported point estimates of pairwise agreement ranging from 0.65 (moderate) to 1.00 (perfect). Carter et al 18 circulated 100 paraffin and fresh frozen histology slides to 5 pathologists.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies on reliability for cytologic and histologic interpretations of anal intraepithelial neoplasia (AIN) specimens are limited. [17][18][19] We, therefore, assessed the interobserver agreement for interpretation of thin-layer cytology and biopsy specimens in the context of an ongoing prospective cross-sectional survey.…”
mentioning
confidence: 99%
“…9,10 Fewer studies, however, have described the cytomorphologic features and diagnostic limitations associated with this new specimen type. [13][14][15] The current study evaluated the use of anorectal cytology in a high-risk population and the cytomorphologic features associated with a variety of anorectal lesions. Detection of abnormalities in ThinPrep slides is more effective than conventional preparations.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are few studies addressing morphologic findings in anal cytology to support this assumption. Scholefield et al 13 reported some guidelines regarding anal cytology but included only 30 anal preparations without histologic correlation or follow-up. Sherman et al 14 described some morphologic features encountered in smears and ThinPrep (Cytyc, Boxborough, MA) preparations from anal specimens, but no histologic or anoscopic correlation was provided.…”
mentioning
confidence: 99%
“…In this example, it is observed, with special attention, the squamocolumnar transition zone after topical application of acetic acid 3%, lesions suspected to be produced by the cytopathic effect of HPV will become whitish and underwent biopsy (26) . The histopathological result of a high resolution anoscopy (HRA) monitored biopsy is considered the goldstandard test for confirming the presence of an anal squamous intraepithelial lesion (35,43) . However, even though HRA is a tool routinely used in the diagnosis of anal lesions, there is little information in the medical literature regarding the success of this medical diagnostic technique regarding the detection of anal cancer precursor lesions.…”
Section: Introductionmentioning
confidence: 99%